Investigating Place Attachment Theory And Its Triggers In Historic Buildings In Different Contexts In Cairo - Fayek, Andrew N.; Kamel, Basil; Khalil, Heba Allah (MAJ - Malaysia Architectural Journal, 2025)
While Cairo is a city with a diversity of buildings of high historical and heritage value, there is lack of awareness of this value, which often results in neglecting those buildings leaving them in a dilapidated status. This research investigates Place attachment (PA) theory and its relation to historic buildings in Cairo. The main objective is to identify the aspects that trigger the sense of attachment to these places to re-instate their value. The research utilizes questionnaires and interviews to study place attachment towards historic buildings in various communities in Cairo (Mosque of Al Sayyida Nafisa, Khanqah of Faraj Ibn Barquq, and the Basilique Notre Dame D’Heliopolis). This process aims to evaluate the needs of different categories of users and what these buildings provide for them, whether it is an economical, religious, psychological, or memorable value. The outcome of this research can be used as a guide to identify what functions are needed in heritage preservation projects to benefit different user groups and to reinstate the value of these buildings.